Implementation and Scale Up of Point of Care (POC) Diagnostics in Resource-Limited Settings - Mashamba-Thompson, Tivani; Drain, Paul K. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Scale up and implementation of new point-of-care (POC) diagnostics is a global health priority to enable the adoption of new evidence-based POC diagnostics and to replicate and extend the reach of POC diagnostics. Global private and public sector agencies have significantly increased their investment in the development of POC diagnostics to meet the unmet needs of patients in resource-limited settings, particularly disease burdened settings with limited access to laboratory infrastructure. However, previous research has demonstrated that the availability of health technologies in these settings does not always guarantee patient-centered outcomes. The applicability, effectiveness and sustainability of diagnostic technologies is affected by the involvement of all stakeholders during planning and implementation, which must be relevant to each specific context and sensitive to local culture. Factors such as infrastructure, resources, values and characteristics of participants can influence the implementation, scalability and sustainability of health interventions such as POC diagnostics. This book, "Implementation and Scale up of Point of Care (POC) Diagnostics in Resource-Limited Settings", presents literature reviews and primary research studies focusing on the implementation and scale up of POC diagnostics in resource-limited settings.